The effect of young marriage on household communication harmony in Medan - Abdul Haris; Marlina; Hasrat Efendi Samosir; Devi Eka Yulita Tarigan (Faculty of Communications Science, Dr. Soetomo University, 2023)
This study aims to determine: The effect of young marriage on household harmony in Medan Sinembah Village, Tanjung Morawa District on the perspectives on Family Communication. The type of research is quantitative research. The population of this study was adolescents who married at a young age in 2019-2020 whose marriage age was 19-20 years, totalling 52 people. Sampling used a total sampling technique, with a sample of 52 people. The data collection instrument used a questionnaire with a Likert scale totalling 15 statements of young marriage variables, including 12 valid items and 3 invalid items. Then 32 statements of household harmony variables including 28 valid items and 4 invalid items. The data analysis technique used descriptive tests, normality and linearity test, and hypothesis testing. The results of this study indicate that there is an influence between the young marriage variable and the household harmony variable with a t count of 3,794 l> 2,008, so it can be concluded that Ho is rejected and Ha is accepted, which means that